Relationship between Surgery and Trauma and Risk of Recurrence in Patients with an Associated First Venous Thrombotic Event: A Nested Case-Control Study - Gregorio, T.; Creeper, K. J.; Pagliani, L.; Providencia, R.; Buzea, A.; Wallenhorst, C.; Weitz, J. I.; Cohen, A. T. (Thrombosis and Haemostasis, 2025)
The duration of anticoagulation treatment for venous thromboembolism (VTE) depends on whether the event was provoked or unprovoked. Major surgery or trauma are well-established major provoking factors associated with a low risk of recurrence, but the magnitude of risk with VTE after minor surgery or trauma is uncertain.To compare the rate of recurrence in patients with VTE provoked by minor surgery or trauma with that in patients with VTE provoked by major surgery or trauma.Nested, case-control study of patients with a first VTE diagnosed within 90 days after major or minor surgery or trauma. Patients with unprovoked VTE or VTE provoked by cancer or nonsurgical risk factors were excluded. Crude and adjusted odds ratios with 95% confidence intervals (CI) were calculated and results were adjusted for potential confounders.A total of 319 patients with recurrent VTE (cases) were matched to 974 patients without recurrence (controls). The incidence of recurrence after VTE provoked by minor surgery (6.5%; 95% CI: 5.6–7.6) was more than double that after VTE provoked by major surgery (3.0%; 95% CI: 2.4–3.6), a difference that remained even after adjustment for known VTE risk factors. There were no differences in recurrence rates between VTE provoked by minor and major trauma.The risk of recurrence is higher in patients with VTE provoked by minor surgery than major surgery. These findings support the concept that the risk of recurrence is higher with minimally provoked VTE than with VTE provoked by major transient risk factors.
Keywords: trauma; surgery; venous thromboembolism; recurrence